GE_GERICHTE A/1479/2024 vom 6. Mai 2024 - GE Cour de justice (2024)
DÉTENTION AUX FINS D'EXPULSION;MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);DÉTENTION PRÉPARATOIRE | LEI.76.al1.letb.ch1; LEI.76.al1.letb.ch3; LEI.76.al1.letb.ch4; LEI.75.al1.letb; LEI.75.al1.letg; LEI.76.al1.leta